Evaluasi Implementasi Rekam Medis Elektronik Rawat Inap Menggunakan Metode PIECES di RSUD Siti Fatimah Provinsi Sumatera Selatan - M. Ariq Dwi Rizky Paganini (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aimed to evaluate the implementation of inpatient Electronic Medical Records (EMR) at Siti Fatimah Regional Hospital, South Sumatra Province, using the PIECES framework, which consists of Performance, Information, Economics, Control, Efficiency, and Service aspects. The study employed a descriptive qualitative approach through observations and in-depth interviews involving nine medical record officers in the inpatient unit. The findings indicated that the EMR system demonstrated good performance in terms of response time and operational support; however, several issues remained, particularly regarding incomplete data entry and inconsistencies in information storage. From the information aspect, the system was considered capable of providing accurate and relevant information, although certain patient data were not optimally recorded in the electronic system. Economically and operationally, the EMR implementation contributed to improving work efficiency and reducing administrative burden, yet further optimization of human resources and system infrastructure is still required. In terms of control and service, the system provided adequate data security and supported healthcare service delivery effectively. Overall, the implementation of the EMR system in inpatient services has functioned adequately, but continuous system improvement and evaluation are necessary to enhance the quality and effectiveness of hospital information services.